2013
DOI: 10.1016/j.ajpath.2012.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma Cells Use Thy-1 (CD90) on Endothelial Cells for Metastasis Formation

Abstract: The cell adhesion molecule Thy-1 (CD90) mediates the adhesion of melanoma cells to activated human endothelial cells (EC) via the interaction with the αvβ3-integrin on the tumor cells in vitro. Here, we report a strong expression of Thy-1 on both blood vessel and lymphatic EC in melanoma and melanoma metastases. Vascular endothelial growth factor and tumor necrosis factor-α were identified as inducers of Thy-1 expression on EC in vitro. The physiological role of Thy-1 for lymphogenic and hematogenic metastasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
57
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 42 publications
(49 reference statements)
2
57
0
Order By: Relevance
“…To further determine the prognostic value of CD90, we analyzed relationships between CD90 and clinicopathologic parameters. We also found positive correlation between CD90 and several clinicopathologic parameters: pathological grade, satellite lesion and PVTT, which was consistent with the concept that CD90 promoted metastatic properties of tumors [12,29]. We divided HCC patients into two groups according to CD90 expression and discovered that it could be an independent predictor for prognosis.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…To further determine the prognostic value of CD90, we analyzed relationships between CD90 and clinicopathologic parameters. We also found positive correlation between CD90 and several clinicopathologic parameters: pathological grade, satellite lesion and PVTT, which was consistent with the concept that CD90 promoted metastatic properties of tumors [12,29]. We divided HCC patients into two groups according to CD90 expression and discovered that it could be an independent predictor for prognosis.…”
Section: Discussionsupporting
confidence: 60%
“…In humans, it is mainly expressed on several types of cells including: broblasts, blood stem cells and activated microvascular endothelial cells (ECs) [9,10]. Nevertheless, high level of CD90 expression has also been observed in CAFs [11][12][13]. Sukowati et al [14] found that CAFs isolated from human HCC tissues were positive for CD90.…”
mentioning
confidence: 99%
“…We did not observe the presence of HA-tagged NAMPT within non-neuronal cells in the mouse brain ( Figure 1D), although Thy-1 has been reported to be expressed in endothelial cells and in white blood cells such as T lymphocytes, 21,22 two cell types that are intimately involved in the pathogenesis of ischemic stroke. However, T-cell infiltration into the brain usually occurs 3 days after cerebral ischemia, 23 whereas NAMPT already exerted WM protection effect within this timeframe in our studies.…”
Section: Discussionmentioning
confidence: 92%
“…It has recently been reported that Thy-1 mediates melanoma cell adhesion to the endothelium, facilitating tumour metastasis in the B16/F10 model 12 . This interaction is mainly attributed to integrin a v b 3 engagement; however, the downstream signalling responses and adhesive phenotype of cells engaging Thy-1 are less well known.…”
Section: Resultsmentioning
confidence: 99%
“…Thy-1 also binds heparin sulphate proteoglycans (HSPGs), including syndecan-4 (Syn4), through a conserved polycationic motif in the C-C' strand loop motif 7,10 . In patients with metastatic melanoma, Thy-1 is highly expressed on both the venous and lymphatic endothelium, where it facilitates metastasis in experimental models of melanoma 11,12 . Thy-1 expression is also enriched on human tumour-associated endothelium and lymphatic vessels 13 .…”
mentioning
confidence: 99%